Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3026004
|View full text |Cite
|
Sign up to set email alerts
|

Essence

Abstract: The sense of smell is perhaps the most pervasive of all senses, but it is also one of the least understood and least exploited in HCI. We present Essence, the first olfactory computational necklace that can be remotely controlled through a smartphone and can vary the intensity and frequency of the released scent based on biometric or contextual data. This paper discusses the role of smell in designing pervasive systems that affect one's mood and cognitive performance while being asleep or awake. We present a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…It can be worn as a necklace or a clip and can release odors based on heart rate and brain activity ( Fig. 2 , Amores & Maes, 2017 ). The device is wireless and connects to physiological sensors as well as the Muse EEG headband; it monitors heart and breathing rate from sensors integrated into the device ( Amores, Hernandez, Dementyev, Wang, & Maes, 2018 ).…”
Section: Simulating Worlds Through Sensory Stimulationmentioning
confidence: 99%
“…It can be worn as a necklace or a clip and can release odors based on heart rate and brain activity ( Fig. 2 , Amores & Maes, 2017 ). The device is wireless and connects to physiological sensors as well as the Muse EEG headband; it monitors heart and breathing rate from sensors integrated into the device ( Amores, Hernandez, Dementyev, Wang, & Maes, 2018 ).…”
Section: Simulating Worlds Through Sensory Stimulationmentioning
confidence: 99%
“…Essence is a wearable olfactory display developed in previous work [10]. It has embedded computational capabilities, so that the frequency and intensity of scent release can be controlled via Bluetooth using a smartphone application.…”
Section: B Olfactory Necklacementioning
confidence: 99%
“…For that reason, this article introduces a lightweight and wearable system integrating a virtual reality experience, an olfactory necklace [10], and a low-cost, wearable EEG headband to promote relaxation (see Figure 1). We believe that our system can contribute in the field of ubiquitous computing and wearable technology by integrating the already proven effectiveness of scent for relaxation and immersive virtual reality therapy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…We chose the chest as it provides better breath-sensing accuracy, given how much people move their wrists (e.g., typing, using a phone) during the day. Zeagler et al [61] indicated the upper part of the chest as a proper candidate to position wearables, and prior work proposes wearable pendants [3,13,46] to act as either input or output.…”
Section: Body Positioningmentioning
confidence: 99%
“…The breathing of the participants was covertly monitored with the pendant, as it was in constant contact with the chest during the experiment. The signals were streamed to the computer and synchronized with the beginning and end of each 40s trial using the lab streaming layer (LSL) protocol 3 .…”
Section: Breathing Analysismentioning
confidence: 99%